MENINGKATKAN SELF-EFFICACY MATEMATIS SISWA PADA PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN BRAIN BASED LEARNING - Rusyda, Nurul Afifah; Suherman, Suherman; Suhendra, Suhendra; Rusdinal, Rusdinal (Media Pendidikan Matematika, 2020)
This research was conducted because the students' self-efficacy in mathematics was still low. The Brain Based Learning approach is expected in solving this problem. The purpose of this study was to determine and analyze the increasing in self-efficacy of students who received the Brain Based Learning (BBL) approach in mathematics. This study is a quasi-experimental study with a nonequivalent control group design. The population of this study were all students of grade VII at a junior high school in Padang City. The sample was determined by purposive sampling technique. The data collection instrument in this study was a non-test (questionnaire). Questionnaires are used to measure students' mathematical self-efficacy. The questionnaire is based on indicators of self-efficacy. The self-efficacy questionnaire consists of 28 questionnaire items. The questionnaire was given before being given treatment and after being given treatment. The treatment given was in the form of mathematics learning based on the BBL approach. The result of this study is that the increase in self-efficacy of students who get the BBL approach learning is significantly better than learning with the conventional approach as a whole.